Inventory control policy of preventive lateral transshipment between retailers in multi periods - Qingren He; Bin Dan; Ru Liu (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Preventivelateral transshipment can respond to customers who will choose a substitute or to give up when the product is out of stock. Motivatedby the common practice, adecision-making model of preventive lateral transshipment with multi sellingperiods is developed. The purpose of the paper is to explore the optimal preventive lateral transshipment policy with multi selling periods. Design/methodology/approach: With adiscrete-time dynamic programming model, we take a dynamic programming approach and adopt backward induction to analyze two retailers' preventive lateral transshipment policy. Findings: The optimal preventivelateral transshipment policy is a threshold policy which depends on both theremaining selling periods and inventory level. The above properties ensure thattwo retailers can control inventory with preventive lateral transshipment. Practical implications: The retailer can adjust inventory via the thresholdtype policy. The simple decisionrule which compares on-hand inventory level with the critical inventory level can be used to control inventory by preventive lateral transshipment. Originality/value: A discrete-timedecision-making model of preventive lateral transshipment policy isformulated. This model takes consideration of multi selling periods, which is different from most existing researches on preventive lateral transshipment.
Keywords: 650; preventive lateral transshipment; the transship-up-to level; the transship-down-to level; inventory control policy; multi selling periods